دراسة مقارنة في الاتزان الحركي بين الذكور والإناث في مرحلة التعليم الابتدائي بعمر (11 – 12) سنة - R qaydar; ميادة حمد لله طه; إسراء ثروت غانم (مجلة ابحاث كلية التربية الاساسية)
study aims at - Identifying difference in motor balance between males and females in  primary education stage pupils aging (11-12) years. To achieve objectives of research, the researchers used descriptive approach in comparative study style, Sample consisted of male and female pupils in Alfraheede Primary School for Boys and Girls for the academic year (2023 - 2024), (30) male and female out of a total of (100) pupils. Two pilot experiments were conducted to verify experiment conditions. Arithmetic means, standard deviation, percentage, simple correlation coefficient (Pearson), and T-test for independent samples were used as statistical means. The most important results of the research were as follows: - Males surpassed females in  modified Bass test of moving balance in primary education stage pupils at the age of (11-12) years.